Biochar as a strategy to manage stem rot disease of groundnut incited by Sclerotium rolfsii - Manasa, Ramaraju; Devi, R. Sarada Jayalakshmi; Vemana, Kuruba; John, K.; Rao, G. Rama; Anubhava, P. J.; Vidyashree, L. K.; Sri Ananth, Kurella; Santosh, Kale; Sawargaonkar, Gajanan; Sudini, Hari Kishan (Frontiers in Agronomy, 2024)
Due to the pathogen’s ability to survive in the soil for longer durations, soil-borne diseases are often difficult to control. This study investigates the multifaceted impacts of biochar on the management of stem rot disease in groundnut and its influence on soil properties and microbial communities. The effects of biochar at different concentrations, such as 0%, 1%, 3%, and 5% on groundnut stem rot disease incited by Sclerotium rolfsii were evaluated thoroughly. Under laboratory conditions, biochar exhibited no direct inhibitory effects on S. rolfsii at varying concentrations but revealed an indirect suppression of sclerotial body production, suggesting a concentration-dependent influence on pathogen resting structures. Further, it was observed that biochar treatments effectively delayed symptom onset and reduced disease progression in groundnut plants, with significant variation observed among genotypes and biochar concentrations. Notably, interactions involving genotypes ICGV 171002 and ICGV 181035 with BC2 + Sr (3% conc. of biochar + S. rolfsii) and BC3 + Sr (5% conc. of biochar + S. rolfsii) treatments showed superior efficacy in disease reduction under controlled conditions. Field evaluations confirmed these findings, highlighting genotype-specific responses to biochar treatments. However, no significant difference was observed between BC2 + Sr (3%) and BC3 + Sr (5%) treatments in managing stem rot disease compared to controls. Biochar application significantly increased soil nutrient levels, including nitrogen, phosphorus, and potassium, and increased soil organic matter content, EC, pH, emphasizing its potential to improve soil fertility. Overall, these findings highlight the potential benefits of biochar for sustainable agriculture through disease management, soil nutrient enrichment, and microbial modulation, warranting further investigation into optimal application strategies across different agricultural contexts.